2016
DOI: 10.3390/jintelligence4030008
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fluid Intelligence by Components of Reaction Time Distributions from Simple Choice Reaction Time Tasks

Abstract: Mean reaction times (RT) and the intra-subject variability of RT in simple RT tasks have been shown to predict higher-order cognitive abilities measured with psychometric intelligence tests. To further explore this relationship and to examine its generalizability to a sub-adult-aged sample, we administered different choice RT tasks and Cattell's Culture Fair Intelligence Test (CFT 20-R) to n = 362 participants aged eight to 18 years. The parameters derived from applying Ratcliff's diffusion model and an ex-Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
(82 reference statements)
4
28
3
Order By: Relevance
“…Interestingly, while the EEA construct has been extensively invoked to explain task performance in hundreds of studies, the mechanistic basis of individual-differences in EEA, and how these differences relate to differences in other cognitive constructs, are much less explored (but see 29,48). Several studies using perceptual decision tasks find drift rates are related to general intelligence [54][55][56][57] , similar to the pattern we found in the present study. But, again similar to prior work, the correlations we found in this study between EEA and general intelligence were moderate in size, with individuals' general intelligence explaining less than 25% of the variance in EEA in this sample.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, while the EEA construct has been extensively invoked to explain task performance in hundreds of studies, the mechanistic basis of individual-differences in EEA, and how these differences relate to differences in other cognitive constructs, are much less explored (but see 29,48). Several studies using perceptual decision tasks find drift rates are related to general intelligence [54][55][56][57] , similar to the pattern we found in the present study. But, again similar to prior work, the correlations we found in this study between EEA and general intelligence were moderate in size, with individuals' general intelligence explaining less than 25% of the variance in EEA in this sample.…”
Section: Discussionsupporting
confidence: 78%
“…Higher drift values, thus, indicate that the process is faster and ends more frequently at the correct threshold. It has been shown that easier trials feature higher drift rates (e.g., Ratcliff, 2014;Voss et al, 2004), as do more intelligent individuals (Ratcliff, Thapar, & McKoon, 2010;Schmiedek, Oberauer, Wilhelm, Süß, & Wittmann, 2007;Schubert, Hagemann, Voss, Schankin, & Bergmann, 2015;Schulz-Zhecheva, Voelkle, Beauducel, Biscaldi, & Klein, 2016). The decision process is influenced not only by the drift rate but also by additive Gaussian noise (the standard deviation of this noise is termed the diffusion constant and is often described as a scaling parameter of the diffusion model).…”
Section: Introduction To Diffusion Modelingmentioning
confidence: 99%
“…Therefore, individuals with lower EEA would be expected to display reduced accuracy rates and more variable RTs across a range of cognitive tasks. (94)(95)(96)(97)(98)(99). Additionally, EEA measured via relatively simple choice tasks nonetheless correlates strongly with EEA measured in more complex tasks, and also predicts better working memory ability and general intelligence (95)(96)(97)(98)(99)(100)(101)(102)(103).…”
Section: Efficiency Of Evidence Accumulation As a Foundational Indivimentioning
confidence: 99%